If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + -9 = 16y + 19 Reorder the terms: -9 + 12y = 16y + 19 Reorder the terms: -9 + 12y = 19 + 16y Solving -9 + 12y = 19 + 16y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16y' to each side of the equation. -9 + 12y + -16y = 19 + 16y + -16y Combine like terms: 12y + -16y = -4y -9 + -4y = 19 + 16y + -16y Combine like terms: 16y + -16y = 0 -9 + -4y = 19 + 0 -9 + -4y = 19 Add '9' to each side of the equation. -9 + 9 + -4y = 19 + 9 Combine like terms: -9 + 9 = 0 0 + -4y = 19 + 9 -4y = 19 + 9 Combine like terms: 19 + 9 = 28 -4y = 28 Divide each side by '-4'. y = -7 Simplifying y = -7
| 9x-3=3+8x | | 7x+3y=16 | | 23-6x=-61 | | v(4v-24)=-6 | | -8y+5=-9y+3 | | h^2+26h-10=0 | | -6y+4=7y+5 | | 27x+13x=73 | | 3x^2-3x+5=0 | | 5p+5=7-4p | | x-2x+5=5 | | X^2+11x+13=0 | | (3x+7)(x+1)=10 | | 9-41= | | x^2-30x+125=0 | | 2x(x+8)+15=0 | | g^2-8g+11=0 | | 2x-5y=1 | | 5(x+6)=8+5x | | 3x^2+2x+8=0 | | d^2+22d+121=18 | | 8x+3y=8 | | 9x^10=4x^9+41 | | b^2-8b+17=7 | | 15x^2=3x+7 | | 4p+3=10+3p | | 4p+3=10+3 | | 7x+2y=2 | | 4x+16-18=-8x+2 | | 6.8x-1=5.8x | | 60x^2*y^4=x | | 5x+y=13 |